2012
DOI: 10.7863/jum.2012.31.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Complete Placenta Previa

Abstract: Does Prior Cesarean Delivery Matter?lacenta previa complicates approximately 0.4% of all thirdtrimester pregnancies. Risk factors for placenta previa include prior cesarean delivery, history of placenta previa with a prior pregnancy, increasing parity, advanced maternal age, prior uterine surgery, tobacco use, and multiple gestations. Prior cesarean delivery is one of the most important risk factors for development of placenta previa, and the risk of placenta previa increases as a woman has more cesarean deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In studies by Lal et al [11] and Eichelberger et al [19], migration rates in anteriorly situated placentae showed no difference from that of posteriorly situated ones. However, Magann et al [16] showed a higher possibility of resolution in posteriorly located previa, and attributed the phenomenon to the disproportion in the growth of uterine smooth muscles between anterior placentas and posterior ones.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…In studies by Lal et al [11] and Eichelberger et al [19], migration rates in anteriorly situated placentae showed no difference from that of posteriorly situated ones. However, Magann et al [16] showed a higher possibility of resolution in posteriorly located previa, and attributed the phenomenon to the disproportion in the growth of uterine smooth muscles between anterior placentas and posterior ones.…”
Section: Discussionmentioning
confidence: 84%
“…However, Magann et al [16] showed a higher possibility of resolution in posteriorly located previa, and attributed the phenomenon to the disproportion in the growth of uterine smooth muscles between anterior placentas and posterior ones. Conversely, other studies believed that placenta previa with an anteriorly located placenta was more likely to migrate, and the migration was secondary to a thinner lower uterine segment on the anterior portion of the uterus, leading to a more pronounced upward migration [11,25]. While Lal et al [11] demonstrated that placental location did not influence the resolution of placenta previa.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations